The contribution of women in engineering during the COVID-19 pandemic through indexed scientific publications - Reinoso, O.A.R.; Ordóñez-Avila, J.L.; Romero, A.G.G.; Durón, R.M. (My University, 2023)
Engineering played a fundamental role during the pandemic, helping to develop new technology to diagnose and trace cases, as well as to improve digital health in many aspects. This work aims to make visible the contributions of Honduran women in engineering by analyzing scientific publications in journals indexed in local or international databases. A descriptive cross-sectional study was carried out with a bibliometric approach to characterize the scientific production on COVID-19 in Honduras in relation to engineering. The results showed a greater predominance of women in publications in non-Scopus journals, suggesting fewer publication opportunities or capacities. The publications found were headed by women in 36.8% of cases, but due to the nature of data, academic degrees were not available, and it is not clear how many were engineers or women studying engineering. It is recommended to encourage women engineers or those who are in the final stages of undergraduate studies or postgraduate courses to seek to publish in indexed journals and alike, to join professional engineering organizations such as IEEE, ACM, ASME among other, in order to increase their scientific networks and leadership. © 2023 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.
Keywords: COVID-19; Indexed Publications; Women in Engineering